Sport-based risk management: shaping motivated, responsible and self-governing citizen subjects - Ekholm, David (European Journal for Sport and Society, 2017)
The Sport Programme, initiated by municipal administrators and managed by a social entrepreneur, is a Swedish sport-based intervention promoted as a response to social problems of crime and segregation in a targeted urban area. The article examines the manager and coaches' presentation of the programme with respect to how pedagogical governing techniques are assumed to promote social change and how desirable citizen subjects are constructed for social inclusion. A variety of statements are analysed from a governmentality perspective. It is concluded that, although problems are assumed to be caused by structural segregation, the intervention targets individual change and risk management. Presumably, subjects are provided with motivational powers that are shaped by role models and applied in 'choosing the right track', navigating among risks and averting problems and exclusion. By representing problems as risks, avoidance is formed as an individual opportunity. This technology of individual agency is aimed at shaping motivated, responsible and self-governing citizen subjects, thus representing subjects as being responsible for their own welfare and inclusion. With respect to sport as a means of responding to social problems, the article provides reflections on and empirical accounts of the conditions of welfare provision and social work under advanced liberalism.